2015
DOI: 10.2105/ajph.2014.302519
|View full text |Cite
|
Sign up to set email alerts
|

Work Safety Climate, Safety Behaviors, and Occupational Injuries of Youth Farmworkers in North Carolina

Abstract: Youth farmworkers perceived their work safety climate as being poor. Although additional research is needed to support these findings, these results strengthen the need to increase employer awareness to improve the safety climate for protecting youth farmworkers from harmful exposures and injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 52 publications
4
43
0
1
Order By: Relevance
“…Consistent with research, higher general safety climate is associated with increased PPE use . Results of general safety climate and HPD use specifically have been mixed.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Consistent with research, higher general safety climate is associated with increased PPE use . Results of general safety climate and HPD use specifically have been mixed.…”
Section: Discussionsupporting
confidence: 54%
“…Safety climate refers to workers’ perceptions about the importance management gives to organizational policies, procedures, and practices regarding safety . Safety climate has been positively linked to safety outcomes as well as safety behaviors such as increased PPE use . Associations have been observed between higher general safety climate and increased PPE use, although few have examined HPD use specifically …”
Section: Introductionmentioning
confidence: 99%
“…For instance, adolescent farmworkers in the US have been observed to engage in riskier work practices than their adult counterparts. These practices include engaging in higher pesticide exposure habits, such as less hand washing, wearing wet clothing, or wearing shorts instead of long pants (Kearney et al, 2015). In order to develop potential interventions to reduce CPF exposure among adolescents, determinants of exposure must be identified.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research revealed a positive association between safety climate and seafarers' safety behavior [22][23][24]. Some research proved that safety climate is positively and significantly associated with safety behaviors [25][26][27]. Seo et al [28] pointed that safety climate had a significant direct effect on safety behavior.…”
Section: Hypothesismentioning
confidence: 99%